An intertidal crabs of Bruit and Patol Islands - Nur Nasuha, Mohd Noramin Chang (Universiti Malaysia Sarawak, (UNIMAS), 2015)
study on crab's community structure was conducted in Bruit and Patok Islands. The sampling was carried out from 20 to 23 August 2014. The objectives of the study are to identify the species composition, diversity, evenness and richness of crabs at intertidal areas of Bruit and Patok Islands and to determine the relationships of physico-chemical and sediment parameters with species density of Brachyuran crabs. The samples were collected on the intertidal areas of the island. Six stations were established around the islands. At each station, 100 m2 of quadrate was used to collect the crab samples. Within the quadrate, five sub-quadrate of Im 2 were made. The pH, temperature, salinity and dissolved oxygen of hole water were measured using suitable portable equipment. Crabs specimens was counted and identified. A total of 6 families consist of 19 species were recorded. The Brachyuran crabs density was correlated with physico-chemical parameters of the water and sediments in Bruit and Patok Islands. However, their correlations were not significance.